PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH (PROBLEM BASED INSTRUCTION) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 002 BANTAIAN - Nurhajijah, Nurhajijah; Putra, Zetra Hainul; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The research aims to increase learning process and students’ mathematical result in grade IV SDN 002 Bantaian in academic year 2014/2015. The subject of this research is students at grade IV SDN 002 Bantaian which consist of 28 students, 11 girls and 17 boys. The researchers use a classroom action research which has two cycles which was conducted on March 24th to April 4nd 2015. The data show that either learning process or students’ mathematical achievement increased. This was found from students and teacher’s scores in learning process increased. First cycle at the first meeting teacher’s activity was 67,5% categorized as enough and increased 10% at the second meeting as 77,5% categorized as good. Meanwhile at the second cycle at the first meeting, the percentage of teacher’s activity increased as 87,5% categorized as good and in the second meeting it increased 5% so the percentage became 92,5% categorized as very good. While students’ activities in learning process also increased at the first cycle in the first meeting. The percentage of students activities was 57,5% categorized as less and the second meeting it increased as 20% so became 77,5% categorized as good, at the second cycle in the first meeting it increased to 87,5% categorized good. At the second meeting the percentage of students’ activities increased 5% became 92,5% categorized as very good. However students‘ achievement also increased. The basic score of daily examination increased 6,38% into the first cycle which 19 students passed and 9 students failed. The classical completeness in the end of the first cycle was 67,86% and the average score was 68,57. The second daily examination also increased from basic score as 17,47% which 24 students passed and 4 students failed. The ending of second daily examination was 85,71% and the everage was 75,71. Based on the explanation it can be concluded that the implementation of Problem Based Intruction (PBI) model can improve mathematical learning result of grade IV SDN 002 Bantaian.Keywords: Prolem Based Instruction Model, Mathematical Learning Result